The Rising Price of Physicians' Services: A Clarification - Brown, Douglas; Feldstein, Martin; Lapan, Harvey (The Review of Economics and Statistics, 1974)
Several years ago, one of us presented a model of the market for physicians' services (Feldstein, 1970). In a subsequent comment, Brown and Lapan ( 1972) raised several questions about the model and the conclusions. Unfortunately, this comment and the reply by Feldstein ( 1972) left a number of issues unsettled. Some of the disagreement was based on misunderstanding and on drawing infer ences from different theoretical models. After the publication of the comment and reply, we continued to pursue the basis of our disagreements. The cur rent note is an attempt to clarify the issues that were raised but not resolved in the previous ex change.